Electromagnetic Wave Absorbing Materials on Radar Frequency Range - Yana Taryana; Azwar Manaf; Nanang Sudrajat; Yuyu Wahyu (Jurnal Keramik dan Gelas Indonesia, 2019)
Radar absorbing material (RAM) is a material that which can absorb and reduce energy of electromagnetic wave. Recently, RAMs are widely used as an isolator to protect electromagnetic wave interference (EMI) caused by external electromagnetic field and electromagnetic waves generated by radio frequency (RF) components that disturb the performance of a radio system. Whilest, the most strategic function is as anti-radar coating material to supply the needs of military systems such as aircraft, combat ships and other equipments. Generally, RAM must be resistive, magnetic and dielectric. Absorption at the resonant frequency region is indicated by the permitability and permeability values of the material. The Most literature has reported that the basic material which has the potential to absorb electromagnetic waves is ferrite-based magnetic material, namely barium hexaferrite and strontium hexaferrite. Therefore, the current development of research leads to modification and engineering of the material structure so that it is expected to obtain the right parameters with a maximum absorption rate. Generally, RAMs construction design are grouped on the impedance matching and resonant absorber types.